A novel robust and high‐throughput method to measure cell death in Nicotiana benthamiana leaves by fluorescence imaging. (23rd August 2021) - Xi, Yuxuan; Chochois, Vincent; Kroj, Thomas; Cesari, Stella
Abstract: Assessing immune responses and cell death in Nicotiana benthamiana leaf agro‐infiltration assays is a powerful and widely used experimental approach in molecular plant pathology. Here, we describe a reliable high‐throughput protocol to quantify strong, macroscopically visible cell death responses in N. benthamiana agro‐infiltration assays. The method relies on measuring the reduction of leaf autofluorescence in the red spectrum upon cell death induction and provides quantitative data suitable for straightforward statistical analysis. Two different well‐established model nucleotide‐binding and leucine‐rich repeat domain proteins (NLRs) were used to ensure the genericity of the approach. Its accuracy and versatility were compared to visual scoring of the cell death response and standard methods commonly used to characterize NLR activities in N. benthamiana . A discussion of the advantages and limitations of our method compared to other protocols demonstrates its robustness and versatility and provides an effective means to select the best‐suited protocol for a defined experiment. Abstract : We provide a high‐throughput method to quantify cell death in Nicotiana benthamiana agro‐infiltration assays relying on the measurement of leaf red fluorescence decline upon induction of cell death.